Specific Aspects of Youth Tourism Development in Developed Countries - Islomova Dilrabo Salomovna1 (European Journal of Life Safety and Stability (2660-9630), 2024)
Youth tourism represents a significant and dynamic segment of the global travel industry, driven by young travelers’ desires for adventure, cultural exchange, and educational experiences. This study explores the specific aspects of youth tourism development in developed countries, combining quantitative survey data from 1,200 respondents with qualitative insights from interviews with 15 industry experts. The analysis reveals key strategies in marketing and promotion, the importance of affordable travel options, and the appeal of cultural and educational programs. The findings also highlight the necessity of comprehensive safety and support services and address the challenges posed by economic constraints, changing preferences, and sustainability concerns. By integrating these insights, the study offers practical recommendations for stakeholders to enhance youth tourism and cater to the evolving needs of young travelers.